Chemical composition, antimicrobial and antioxidant activity of the essential oil of leaves of Eugenia involucrata DC. (Bioscience Journal, 2020)
In the Myrtaceae family, the species Eugenia involucrata DC., popularly known as "cerejeira-do-mato", is traditionally used for the antidiarrheal and digestive action of its leaves. However, no studies were found in the literature regarding its antimicrobial and antioxidant potential. In this context, the objective of the present study was to determine the chemical composition by gas chromatography coupled to mass spectrometry (GC-MS) to evaluate the antimicrobial activity by the broth microdilution technique and the antioxidant activity by the 2,2-diphenyl-1-picryl-hydrazila (DPPH) method of the essential oil of E. involucrata leaves. GC-MS identified 28 compounds, all sesquiterpenes, corresponding to 89.41% of the essential oil. The antimicrobial activity of the essential oil was observed for all Gram-positive bacteria tested (Staplylococcus epidermidis, Enterococcus faecalis, Bacillus subtilis and Staplylococcus aureus) and for yeast Candida albicans. The essential oil presented a reduction capacity of DPPH up to 66.81%, evidencing its antioxidant potential. It is suggested that the antimicrobial and antioxidant action of E. involucrata essential oil is related to the presence of the major compounds, elixene (26.53%), β-caryophyllene (13.16%), α-copaene (8.41%) and germacrene D (7.17%).